Efficacy of a New Non-drug Acne Therapy: Aloe Vera Gel Combined With Ultrasound and Soft Mask for the Treatment of Mild to Severe Facial Acne - Zhong, Hongyu; Li, Xiang; Zhang, Wanqi; Shen, Xiaoxiao; Lu, Yuangang; Li, Hongli (Frontiers in Medicine, 2021)
Background: Acne is a chronic disorder that affects almost 80% of adolescents and young adults, causing psychological and emotional distress. However, the current treatments for acne are either ineffective or have many side effects. This study was designed to confirm and objectively quantify the effect of a new nondrug combined therapy on acne. Methods: This study innovatively utilized ultrasound, which enhanced the absorption of aloe vera gel, and soft mask to make a purely physical method without any drugs. In both the treatment group and control group, the number of papules/pustules and the area of hyperpigmented lesions were counted, and a smart mirror intelligent face system was used before and after the combined therapy. Alterations in the skin functional index were recorded and analyzed statistically. Results: In the treatment group, the combined therapy significantly reduced the number of papules and the area of hyperpigmented lesions and improved skin roughness and local blood circulation. In the control group, there was no obvious improvement over 2 months. Conclusion: This study suggests that the new nondrug combined therapy significantly improved acne, which provided experimental evidence and treatment guidance for patients with mild to severe acne, especially patients with moderate acne. This new therapy may possibly be an appropriate method for patients who seek topical treatments with mild side effects and low antibiotic resistance rates.